(untitled) (Research, Society and Development, 2023)
The furcation defects is related to the presence of bone resorption and loss of attachment in the interradicular region as a consequence of periodontal disease. They are difficult places of immunity and with several treatment options. Objective: to verify, through a narrative review, the applicability of platelet-rich fibrin in the treatment of grade II furcation defects. Methodology: studies in English were selected, from 2012 to 2022, indexed in PubMed / Medline and Lilacs and Cochrane databases that used PRF to treat grade II furcation defects alone or combined with other materials. First, a screening was performed by title followed by reading the abstracts. After verifying a relationship with the theme, the articles were viewed in full by a single researcher. Discussion: studies report that the use of PRF adjuvant to other biomaterials in class II furcation defects seems to be significantly (p<0.01) beneficial for reducing probing depth and gain in clinical hospitalization compared to bone grafts and too much materials when they are used alone. Conclusion: PRF has been identified as a promising biomaterial in the process of tissue immunity in grade II furcation defects.